Searching for the sources of method. Some remarks on Ginzburg’s circumstantial paradigm - Sierotowicz, Tadeusz (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2006)
This paper is a short introduction to C. Ginzburg's article on a circumstantial paradigm.